Terapi Aktivitas Kelompok (TAK) Stimulasi Sensori Terhadap Tingkat Depresi Lansia: Sensory Stimulation Group Activity Therapy (TAK) Against Depression Levels in the Elderly - Afifah, Dian Nur; Susanto, Trully Eko (Universitas Muhammadiyah Sidoarjo, 2016)
Depression is a mood disorder characterized by excessive feelings of sadness, depressed, dispirited feeling feel empty feel worthless, hopeless, feels like a failure until there was an idea to commit suicide. The purpose of this study was to determine the effect before and after therapy group activity sensory stimulation on the level of depression in the elderly.The study design is a pre-experiment (one group pretest-posttest). The population of the elderly in UPT of Elderly Social Services of Pasuruan Located In Babat Lamongan. Sampling with simple random sampling as many as 48 people. The collection of data by the guidelines group activity therapy sensory stimulation. Measurements of depression with the Beck Scale & Deck consists of 13 groups of questions. Analysis of the data by Wilcoxon Sign Rank Test.Based Wilcoxon Sign Rank Test with α = 0.05 p value = 0.000 where p<0.05 means that there are significant group activity therapy stimulasi sensory on the level of depression in the elderly In UPT of Elderly Social Services of Pasuruan Located In Tripe Lamongan.Group activity therapy is expected to be used as an alternative in efforts to reduce the level of depression in the elderly and prevent the return rate of depression ever experienced by the elderly.